PANI–WO3·2H2O Nanocomposite: Phase Interaction and Evaluation of Electronic Properties by Combined Experimental Techniques and Ab-Initio Calculation - Adriano de Souza Carolino; Matheus Moraes Biondo; Ştefan Ţălu; Henrique Duarte da Fonseca Filho; Pedro Henrique Campelo; Jaqueline de Araújo Bezerra; Cicero Mota; Hidembergue Ordozgoith da Frota; Vanderlei Salvador Bagnato; Natalia Mayumi Inada; Edgar Aparecido Sanches (Molecules, 2022)
The development of conjugated polymer-based nanocomposites by adding metallic particles into the polymerization medium allows the proposition of novel materials presenting improved electrical and optical properties. Polyaniline Emeraldine-salt form (ES–PANI) has been extensively studied due to its controllable electrical conductivity and oxidation states. On the other hand, tungsten oxide (WO3) and its di-hydrated phases, such as WO3·2H2O, have been reported as important materials in photocatalysis and sensors. Herein, the WO3·2H2O phase was directly obtained during the in-situ polymerization of aniline hydrochloride from metallic tungsten (W), allowing the formation of hybrid nanocomposites based on its full oxidation into WO3·2H2O. The developed ES–PANI–WO3·2H2O nanocomposites were successfully characterized using experimental techniques combined with Density Functional Theory (DFT). The formation of WO3·2H2O was clearly verified after two hours of synthesis (PW2 nanocomposite), allowing the confirmation of purely physical interaction between matrix and reinforcement. As a result, increased electrical conductivity was verified in the PW2 nanocomposite: the DFT calculations revealed a charge transfer from the p-orbitals of the polymeric phase to the d-orbitals of the oxide phase, resulting in higher conductivity when compared to the pure ES–PANI.